(untitled) (Research, Society and Development, 2023)
The study aimed to analyze the influence of Mozart’s Sonata K448 on the auditory memory of mice. From gestation to adulthood, the animals were exposed to music. To assess memory extinction, an aversive conditioning test was used, observing the freezing behavior of mice. Pregnant females listened to the Sonata or ambient sounds for 10 hours daily. After birth, their pups were exposed to the same music for 30 days. Male mice were categorized into three groups: G1-Mozart, G2-Environment and G3-Control, all of which were exposed to different sounds from the 30th to the 107th day. On the 50th day, there was a habituation period, and on the 54th day, G1-Mozart was conditioned with sound and shock, while G3-Control was not. 28 days later, all groups underwent extinction tests. During the first 3 minutes, the same aversive sound was reproduced, measuring the freezing behavior. Subsequently, a recall test was performed by analyzing the freezing time for 2 minutes. The result showed that there was no significant difference between the groups exposed to Mozart and ambient sounds (t(12)=1.19; p=0.256). Over time, all groups reduced freezing. The study suggests that Mozart’s music may have cognitive benefits on memory, but more research is needed to understand the mechanisms involved.